Odpowiedź :
1.
[tex]f(x) = ax + b\\\\\left \{ {{-a + b = -2} \atop {a + b = 2}} \right. \\\\\left \{ {{-a + b = -2} \atop {a = 2-b}} \right. \\\\\left \{ {{-(2-b) + b = -2} \atop {a = 2-b}} \right. \\\\\left \{ {{-2+b+b= -2} \atop {a = 2-b}} \right. \\\\\left \{ {{b=0} \atop {a = 2-b}} \right.\\\\\left \{ {{b=0} \atop {a = 2}} \right.\\\\Odpowiedz: f(x) = 2x[/tex]
2.
[tex]f(x) = -\frac{1}{2} x - \frac{1}{2}\\\\A(\frac{2}{3},0)\\f(\frac{2}{3}) = -\frac{1}{2} * \frac{2}{3} - \frac{1}{2} = -\frac{2}{6} - \frac{1}{2} = -\frac{2}{6} - \frac{3}{6} = -\frac{5}{6} \neq 0\\f(1) = -\frac{1}{2} * 1 - \frac{1}{2} = -\frac{1}{2} - \frac{1}{2} = -\frac{2}{2} = -1 \\f(0) = -\frac{1}{2}*0-\frac{1}{2} = -\frac{1}{2}\\\\Odpowiedz: B,C[/tex]